Flexible wage system in Singapore : acceptability and prospect. - Chen, Weiting. (2011)
The objective of the study was to investigate the acceptability and prospect of Flexible Wage System (FWS) in Singapore, examining impact of union status and establishment size on FWS uptake rate. FWS allows establishments to make necessary adjustments to their wage system according to economic fluctuations, as well as reward employees based on establishment and individual’s performance. Till date, even with FWS available for establishments to adjust their cost, there is still a reliance on Central Provident Fund (CPF) to tide establishments through economic downturn. Given CPF’s safety social net function, it should not be used for cost adjustments, thus there is a need to investigate the relationship between CPF and FWS.